Data-Driven Insights Into Sustainable Village Development in Central Java (Jurnal Bina Praja, 2023)
This study aims to analyze the relationship between village infrastructure and the development performance of villages within the Central Java Province. The research provides crucial insights into the significance of comprehending the role of village infrastructure in enhancing village development performance. In this study, village infrastructure is measured through three dimensions: social, physical, and institutional. The methodology employed in this research utilizes descriptive analysis to depict the characteristics of village infrastructure and village development performance in the Central Java Province. Furthermore, correlation analysis examines the relationship between village infrastructure variables and development performance. The research findings indicate that social, physical, and institutional infrastructure in villages in Central Java exhibit diverse characteristics and weak relationships.
Keywords: village infrastructure; Developed Village Index; Village Original Revenue; Village-Owned Enterprises